Factors associated with adherence to low protein diet among patients with non-dialysed chronic kidney disease at a specialist hospital in Johor, Malaysia - Leong, Sim Kian (2019)
Chronic kidney disease (CKD) has emerged as one of the significant public health issues worldwide. Locally, one in eleven Malaysian adults is diagnosed with CKD. Management of CKD has been primarily focused on delaying the progression to end-stage kidney disease (ESKD). Although the benefits of low protein diet (LPD) on retarding CKD progression is well reported, patients’ adherence remains the main challenge in LPD implementation. In fact, in the local context, literature is scarce on dietary non-adherence, particularly in LPD and its associated factors, thus hamper strategic planning for intervention. Therefore, this present study was undertaken to evaluate the adherence of LPD among CKD patients and investigating a variety of factors that may affect the adherence including socio-demographic factors, medical history, anthropometry measurements, body composition, biochemical markers, dietary knowledge, appetite level, clinical factors, and psychological factors including stress and health locus of control. This study was a cross-sectional study conducted in Hospital Pakar Sultanah Fatimah Muar, Malaysia, on stage 3 to 5 CKD patients. Purposeful sampling was done on patients fulfilling the study criteria. Social and medical history was obtained through an interview using a questionnaire. Anthropometry measurements were done following the International Society for the Advancement of Kinanthropometry (ISAK), and body composition was measured with a body composition analyzer. Dietary intake was evaluated with three days of dietary records. Dietary energy intake (DEI) and dietary protein intake (DPI) were compared with Kidney Disease Outcomes Quality Initiative (KDOQI) recommendations with an LPD adherence rate set at ±20% of recommended intake. Dietary appetite was assessed using the appetite and diet assessment tool (ADAT). Dietary knowledge was assessed using a modified dietary knowledge questionnaire. Perceived stress scale and multidimensional health locus of control were measured with validated questionnaires at the ESKD population. Binary logistic regression analysis was performed between adherent status with investigated variables to determine predicting variables. A total of 113 patients (54% male) with a mean age of 56.3±12.8 years old (age range 22 to 83 years) and mean estimated glomerular filtration rate (eGFR) of 17.5±11.2 mL/min per 1.73m2 were included in the final analysis. Overall, mean DEI and DPI were 22.4±5.9 kcal/kg/day and 0.83±0.28 g/kg/day, respectively. Only 34.5% of patients adhere to the LPD diet, with 59% exceeding the DPI recommendation. Patients were categorized into three groups according to mean protein intake. Patients with DPI <20%, ±20%, and >20% of the recommended value were classified as NADL, AD, and NADH, respectively. A variety of factors significantly associated with LPD adherence including the stage of CKD, higher serum urea level, lower total white blood cell count, better fasting blood glucose, better blood pressure profile, and reduced dietary energy intake. Multivariate logistic regression model shows that CKD patients were 30% less likely to adhere to LPD with each additional day of hospitalization (OR 0.707, 95%CI 0.50-1.00, p=0.048). Patients with higher DEI were 26% less likely to adhere to LPD (OR 0.744, 95%CI 0.65-0.85, p<0.001). CKD stage 4 patients are approximately 70% less likely to adhere to LPD as compared to stage 5 CKD patients (OR 0.318, 95%CI 0.13-0.77, p=0.012). CKD patients having good dietary knowledge scores were 62% less likely to adhere to LPD as compared to patients with poor dietary knowledge (OR 0.380, 95%CI 0.17-0.85, p=0.018). This study shows that LPD adherence among CKD patients is at an alarmingly low rate of 34.5%. Four predicting factors found to be associated with poorer LPD adherence were lower DEI, shorter duration of hospitalization, further progression of CKD, and poorer dietary knowledge scores. Predicting variables from our study suggest that exposure and education of LPD should be started at earlier stages of CKD instead of conservative management for ESKD patients refusing dialysis. Medical nutrition therapy by dietitians should not mainly focus on increasing knowledge alone as it is not predictive of adherence, and higher knowledge may affect adherence negatively. Findings from our study suggest that behavioral changes in an individual are multi-factorial and warrants for future interventional studies with the inclusion of more psychosocial parameters in improving LPD adherence.